2017
DOI: 10.1063/1.4982654
|View full text |Cite
|
Sign up to set email alerts
|

SFG analysis of the molecular structures at the surfaces and buried interfaces of PECVD ultralow-dielectric constant pSiCOH: Reactive ion etching and dielectric recovery

Abstract: Molecular structures at the surface and buried interface of an amorphous ultralow-k pSiCOH dielectric film were quantitatively characterized before and after reactive ion etching (RIE) and subsequent dielectric repair using sum frequency generation (SFG) vibrational spectroscopy and Auger electron spectroscopy. SFG results indicated that RIE treatment of the pSiCOH film resulted in a depletion of ∼66% of the surface methyl groups and changed the orientation of surface methyl groups from ∼47° to ∼40°. After a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similarly, molecular structures at the surface and buried interface of a low-k pSiCOH were examined before and after reactive ion etching (RIE) and subsequent dielectric repair using SFG. It was also found that RIE treatment and repair did not alter the buried pSiCOH interface 47 …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, molecular structures at the surface and buried interface of a low-k pSiCOH were examined before and after reactive ion etching (RIE) and subsequent dielectric repair using SFG. It was also found that RIE treatment and repair did not alter the buried pSiCOH interface 47 …”
Section: Resultsmentioning
confidence: 95%
“…SFG has been successfully applied to investigate the surface and buried interface of low-k thin film coating on silicon 42 47 Low-k materials and copper have been introduced to replace silicon dioxide and aluminum as interconnections in high performance integrated circuits to improve resistance-capacitance delay, minimize crosstalk-noise, enhance signal transmission, and reduce power dissipation. Porous organosilicate (pSiCOH) materials have been extensively used as low-k interlayer dielectric materials 48 , 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, breaking an interface destroys the interfacial interactions, which very likely leads to studying surfaces that are not representative of the original buried interface. Recently, SFG has been employed to study polymer adhesive interfaces and was used to elucidate chemical reactions occurring at the buried polymer/polymer interface in situ in real time. ,, SFG has also been widely used to explore hard/soft interfaces between silica and a variety of polymer materials in situ nondestructively. More details on SFG theory and experiments will be discussed in the Methods section.…”
Section: Introductionmentioning
confidence: 99%